Nuclear localization of prostaglandin E(2) receptors - Bhattacharya, Mousumi (The National Academy of Sciences, 1998)
Prostaglandin E(2) receptors (EP) were detected by radioligand binding in nuclear fractions isolated from porcine brain and myometrium. Intracellular localization by immunocytofluorescence revealed perinuclear localization of EPs in porcine cerebral microvascular endothelial cells. Nuclear association of EP(1) was also found in fibroblast Swiss 3T3 cells stably overexpressing EP(1) and in human embryonic kidney 293 (Epstein–Barr virus-encoded nuclear antigen) cells expressing EP(1) fused to green fluorescent protein. High-resolution immunostaining of EP(1) revealed their presence in the nuclear envelope of isolated (cultured) endothelial cells and in situ in brain (cortex) endothelial cells and neurons. Stimulation of these nuclear receptors modulate nuclear calcium and gene transcription.